The effect of polymorphisms in the Enhancer of split gene complex on bristle number variation in a large wild-caught cohort of Drosophila melanogaster. - Macdonald, S.J.; Pastinen, T.; Long, A.D. (Genetics, 2005)
The Enhancer of split complex [E(spl)-C] in Drosophila encompasses a variety of functional elements controlling bristle patterning and on the basis of prior work is a strong candidate for harboring alleles having subtle effects on bristle number variation. Here we extend earlier studies identifying associations between complex phenotypes and polymorphisms segregating among inbred laboratory lines of Drosophila and test the influence of E(spl)-C on bristle number variation in a natural cohort. We describe results from an association mapping study using 203 polymorphisms spread throughout the E(spl)-C genotyped in 2000 wild-caught Drosophila melanogaster. Despite power to detect associations accounting for as little as 2% of segregating variation for bristle number, and saturating the region with single-nucleotide polymorphisms (SNPs), we identified no single SNP marker showing a significant (additive over loci) effect after correcting for multiple tests. Using a newly developed test we conservatively identify six regions of the E(spl)-C in which the insertion of transposable elements as a class contributes to variation in bristle number, apparently in a sex- or trait-limited fashion. Finally, we carry out all possible 20,503 two-way tests for epistasis and identify a slight excess of marginally significant interactions, although none survive multiple-testing correction. It may not be straightforward to extend the results of laboratory-based association studies to natural populations.